Comparison of Total Suspended Solids (TSS) in the estuary of the Bengawan Solo Gresik River using satellite image data - Argo Nur Sahid; Siti Zainab (CV. Syntax Corporation Indonesia, 2024)
Comparison of Total Suspended Solids (TSS) in Muara Bengawan Solo Gresik River Using Satellite Image Data. The estuary of the Bengawan Solo River, which is in Ujung Pangkah District, has undergone many changes every year. This is influenced by several factors, one of which is the process of settling (sedimentation) from the transport of material carried by river water along the watershed (DAS). Based on this background, efforts are needed to monitor the distribution of Total Suspended Solid (TSS) in the Bengawan Solo Gresik river estuary. The aim of this study is to determine the distribution of Total Suspended Solid (TSS) over 5 years to find the right formula to model the impact of this change, which can be addressed in the future. The method developed below is remote sensing technology with Landsat 8 satellite image data extracting digital number values that are converted into reflectance values to then find the optimal mathematical model algorithm with parameters from Total Suspended Solid (TSS). From the research that has been done, the following results are obtained: the red band reflectance has the best relationship value with TSS In Situ with an R square value of 0.0450. and the appropriate algorithm model for estimating TSS concentrations is the Linear model with the equation Y = 1311.3x + 447.93.